Adipose‐derived stem cells ameliorate erectile dysfunction after cavernous nerve cryoinjury. (July 2015) - Yang, R.; Fang, F.; Wang, J.; Guo, H.
Summary Erectile dysfunction is a common complication following cryotherapy for prostate cancer. In this study, we investigated the efficacy of adipose‐derived stem cells (ADSC) in improving erectile function in a rat model of cavernous nerve (CN) cryoinjury and the possible mechanisms. Male rats were intracavernous (IC) injected with EdU‐labeled ADSC after bilateral CN cryoinjury. Penile tissues were harvested for histology and protein level detection at 1 and 4 weeks after ADSC administration. Erectile function was assessed prior to tissue harvest. We found that erectile function was significantly improved after ADSC treatment via promoting nNOS‐positive nerve regeneration and cavernous tissue recovery. The expression of cleaved caspase 3 (an apoptotic marker) reduced after ADSC treatment. Although few EdU‐labeled ADSCs were visualized within the penis 4 weeks after administration, plenty of EdU‐labeled ADSCs were found around penile dorsal vessels and nerves 1 week after treatment. Furthermore, three neurotrophic factors (NGF, VEGF, and Neurturin) were significantly decreased in Cryo group, and were partially recovered 1 week after ADSC injection. These results suggested that IC injection of ADSC resulted in substantial recoveries of erectile function after CN cryoinjury. The effects may be achieved through the elevated level of neurotrophic factors in penile tissue and subsequent neuroregenerative effects.